Vývoj globálneho diskurzu vzdelávacej politiky a nové sociálne funkcie predškolského vzdelávania - Ondrej Kaščák (Karolinum Press, 2021)
The study analyses the nature of global education governance and the mechanisms of transnational influencing of national education systems today, with an emphasis on early childhood education. Through a discursive analysis of key OECD and EU documents, it clarifies the new conceptualization of the early childhood education and early childhood education sector as such. The conceptualization, based on a prospective and economizing view, is promoted through various reform mechanisms within particular national contexts. The study gives examples of reform movements in Slovakia and Germany. The study confirms the validity of the so-called convergence hypothesis for early childhood education, despite the diversity of early childhood education traditions in Europe.